Patients transferred within a telestroke network for large-vessel occlusion. (September 2022) - Reddy, Sujan T; Savitz, Sean I; Friedman, Elliott; Arevalo, Octavio; Zhang, Jing; Ankrom, Christy; Trevino, Alyssa; Wu, Tzu-Ching
Introduction: In a telestroke network, patients at a referring hospital (RH) with large-vessel occlusion (LVO) are transferred to a comprehensive stroke centre (CSC) for endovascular thrombectomy (EVT). However, a significant number of patients do not ultimately undergo thrombectomy after CSC arrival. Methods: Within a 17-hospital telestroke network, we retrospectively analysed patients with suspected or confirmed LVO transferred to a CSC, and characterized the reasons why these patients did not undergo EVT based on the 2019 American Heart Association guidelines. Results: Of 400 patients transferred to our hub, 68 (17%) were based on vascular imaging at RH. Time from RH arrival to neuroimaging was significantly longer in patients that underwent both computed tomography (CT) and CT angiography of the brain and neck compared to only CT of the brain (53 vs 13 minutes, p < 0.05). Accuracy of anterior circulation LVO (ACLVO) detection based on clinical suspicion was 62% (205 of 332 patients). Among 234 ACLVO patients, overall, 175 (74%) (early window group: 123 (73%) patients and late window group: 52 (80%) patients) met at least one EVT ineligibility criterion. The reasons for EVT ineligibility varied from large core infarct (aspects <6 or core volume >70 cc on perfusion imaging in late window), low National Institutes of Health Stroke Scale (<6), distal occlusion, and poor baseline modified Rankin Scale score (>1). Discussion: Instituting rapid acquisition and interpretation of vascular imaging at RHs for LVO detection and establishing benchmarks for door to vascular imaging is urgently needed for RHs.